Pemberdayaan Perempuan dalam Meningkatkan Ekonomi Melalui Program Pembuatan Minyak Goreng Kelapa di Desa Weranggere, Kecamatan Witihama - Yosefina Keling Sili; Marianus Kleden; Karolus Tatu Sius (Jurnal Nusantara Berbakti, 2024)
The coconut cooking oil-making program is one of the empowerment programs for women to improve the economy by utilizing the potential of existing natural resources. This program was carried out in Weranggere village, Witihama District, East Flores Regency, as one of the solutions for managing the natural potential in the village. The program aims to increase natural resources and process them into a product with a better selling price than before processing. Coconut is one of the natural resources that will be processed to meet the needs of women and become a business opportunity. Through this program, women in the village are given training on processing coconut into quality oil. They were also taught how to have good and attractive packaging and marketing that can be done online through social media. The method carried out is a fiel research, which is carried out by going directly into the field with the purpose of observation and interview. In addition, this program also encourages the formation of women's groups to manage businesses in the village as an economic improvement. This program is also a forum for women to share knowledge, experience, and support. Women's empowerment through the production of coconut cooking oil provides benefits such as increasing skills, business, and income for women in villages, as well as increasing the selling value of the economy and natural resources owned.